2019
DOI: 10.1093/nar/gkz560
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer-mediated enrichment of interacting JMJD3–DDX21 to ENPP2 locus prevents R-loop formation and promotes transcription

Abstract: ENPP2, which encodes for the enzyme autotaxin (ATX), is overexpressed during chronic inflammatory diseases and various cancers. However, the molecular mechanism involved in the ENPP2 transcription remains elusive. Here, in HEK 293T cells, we demonstrated that lipopolysaccharide (LPS) increased the transcription process at ENPP2 locus through a NF-кB pathway and a reduction of H3K27me3 level, a histone repressive mark, by the demethylase UTX. Simultaneously, the H3K27me3 demethylase JMJD3/KDM6B was recruited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Multiple members of the DExD/H helicase family are significantly enriched in cellular DNA/RNA hybrid interactome ( Cristini et al, 2018 ; Wang et al, 2018 ) and are able to resolve R-loops in vitro using their helicase activity ( Hodroj et al, 2017 ; Song et al, 2017 ; Chakraborty et al, 2018 ; Ribeiro de Almeida et al, 2018 ; Mersaoui et al, 2019 ). Suppression of cellular R-loops by this family of helicases is functionally associated with the preservation of genome integrity ( Hodroj et al, 2017 ; Song et al, 2017 ; Cristini et al, 2018 ), transcription promotion ( Argaud et al, 2019 ), transcription termination ( Cristini et al, 2018 ; Mersaoui et al, 2019 ) and class switch recombination ( Ribeiro de Almeida et al, 2018 ). In contrast, some members of this family of helicases, such as DDX1 and DHX9, can also promote R-loop formation by resolving RNA secondary structures, including stable guanine quadruplexes to facilitate pairing of the linearized RNA with its complementary DNA ( Chakraborty et al, 2018 ; Ribeiro de Almeida et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple members of the DExD/H helicase family are significantly enriched in cellular DNA/RNA hybrid interactome ( Cristini et al, 2018 ; Wang et al, 2018 ) and are able to resolve R-loops in vitro using their helicase activity ( Hodroj et al, 2017 ; Song et al, 2017 ; Chakraborty et al, 2018 ; Ribeiro de Almeida et al, 2018 ; Mersaoui et al, 2019 ). Suppression of cellular R-loops by this family of helicases is functionally associated with the preservation of genome integrity ( Hodroj et al, 2017 ; Song et al, 2017 ; Cristini et al, 2018 ), transcription promotion ( Argaud et al, 2019 ), transcription termination ( Cristini et al, 2018 ; Mersaoui et al, 2019 ) and class switch recombination ( Ribeiro de Almeida et al, 2018 ). In contrast, some members of this family of helicases, such as DDX1 and DHX9, can also promote R-loop formation by resolving RNA secondary structures, including stable guanine quadruplexes to facilitate pairing of the linearized RNA with its complementary DNA ( Chakraborty et al, 2018 ; Ribeiro de Almeida et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…DDX21, the DEAD-box 21 members, harboring the typical motif has been implicated in RNA splicing, ribosome assembly, and translation initiation, which participated in the development and progression of a variety of diseases [ 7 , 9 ]. A recent study provided evidence that enhancer-mediated enrichment of novel DDX21 and JMJD3 interaction was necessary for nascent transcript synthesis via the resolution of aberrant R-loops formation in response to inflammatory stimulus [ 10 ]. Notably, recent research confirmed that DDX21 specifically bound to nucleolar small RNA (snoRNA) to localize on nucleoli and then affected the RNA polymerase I (Pol I) complex including POLR1A, POLR1B to regulate rDNA transcription and promoted ribosomal organisms, ribosome biogenesis, and protein translation, thereby promoting cell proliferation in breast cancer [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…2C; Chen Fig. 2C; Argaud et al 2019;Mersaoui et al 2019). Pre-mRNA splicing and RNA export factors appear to help pull nascent RNAs out from R-loops to facilitate RNA processing and transport, thus preventing R-loop accumulation ( Fig.…”
Section: Promoters As Hotspots For Rbp Actionsmentioning
confidence: 99%
“…For example, the RNA helicases DDX21 and DDX5 have been suggested to help resolve R-loop to promote transcription ( Fig. 2C ; Argaud et al 2019 ; Mersaoui et al 2019 ). Pre-mRNA splicing and RNA export factors appear to help pull nascent RNAs out from R-loops to facilitate RNA processing and transport, thus preventing R-loop accumulation ( Fig.…”
Section: Actions and Mechanisms Of Rbps On Chromatinmentioning
confidence: 99%